ISLAMIC COMMUNICATION AND INFORMATION PRINCIPLES IN DIGITAL PLATFORMS: THE CASE OF ONLINE BUYING AND SELLING ON TOKOPEDIA - Rayhaniah, Sri Ayu; Tahir, M.; Karim, Qarinul (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2024)
This research examines the principles of Islamic communication and information in digital platforms in the case of online buying and selling on Tokopedia. The urgency of this research is rooted in the importance of adaptation of Micro, Small and Medium Enterprises (UMKM) actors to digital changes, especially in the COVID-19 pandemic situation. This research uses a qualitative method involving active users of Tokopedia e-commerce from various regions in Indonesia. The results show that principles such as honesty, accuracy of information, free responsibility, fairness, and constructive criticism are implemented in buying and selling transactions on Tokopedia, although there are still challenges in their consistency.